Palladium‐catalysed cross‐coupling reactions for the synthesis of chalcones - Rullah, Kamal; Mohd F. F., Mohd Aluwi; Bohari, M. Yamin; Joon, Ching Juan; Lam, Kok Wai (Wiley-VCH Verlag, 2019)
In this Minireview, we discuss some of the important palladium‐catalysed cross‐coupling reactions utilised in the synthesis of the enone system of chalcones. Examples given here not only exemplify the efficiency and practicality of new C−C bond formation of the enone system via palladium‐catalysed reactions but also reflect some of the revolutionary methods used for the preparation of a more complex and valuable chalcone scaffold which is known to be a privileged structure in the field of medicinal chemistry.